إنتاج الفونت عالي المتانة باستخدام سبائك من الفروسيليكو مغنيزيوم - هترة, علي; أكتع, سمير; جديد, علي (Latakia University Journal -Engineering Sciences Series, 2019)
يقوم هذا البحث بدراسة خطوات عملية إنتاج الفونت عالي المتانة كتطبيق تكنولوجي، وذلك من خلال التعريف بالمواد والمعدات اللازمة، الكميات الدقيقة للشحنة والمواد المضافة وكذلك العوامل والتقنيات التي يجب أخذها بعين الاعتبار عند التطبيق والتنفبذ العملي لعملية الصهر والسكب، كما يتطرق البحث إلى تأثير العوامل المختلفة على تكور الغرافيت في جميع مراحل الإنتاج. ولذلك في هذا العمل تم دراسة شروط إضافة واستعادة المغنيزيوم في أثناء صب المصهور في البوتقة التي تحتوي على المغنيزيوم , كضبط كمية الكبريت والأوكسجين في المصهور، المحافظة على حرارة صب المعدن المنصهر، فصل الخبث عن المصهور قبل السكب في البوتقة، تصميم بوتقة المعدن المنصهر، غطاء المغنيزيوم الموجود على شكل سبيكة، زمن سكب المصهور من الفرن إلى البوتقة، تركيز المغنيزيوم الموجود في البوتقة. This research studies the steps of ductile iron production as a technological application through having knowledge of the necessary materials and structures, the appropriate quantities and the additive materials as well of the factors and the technique that must considered when applying and carrying out the casting and melting processes. The research gets into the influence of the different factors of the spherical graphite in all stages of the process. So in this work, a study has been made for adding and recovering the magnesium conditions during pouring the melted cast in the crucible that contains the magnesium holding up the quantity of sulphur and oxygen in the molten, seizing the temperature of melted cast iron, separating the slag from the molten before casting in the crucible, designing the ladle of the molten metal, covering the exiting magnesium as the shape of alloy, the time of pouring the molten from the furnace to the crucible, and the concentration of the existing magnesium in the crucible